2006
DOI: 10.1007/s10661-006-7086-7
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring in the Boulder River Watershed, Montana, USA: Metal Concentrations in Biofilm and Macroinvertebrates, and Relations with Macroinvertebrate Assemblage

Abstract: Portions of the Boulder River watershed contain elevated concentrations of arsenic, cadmium, copper, lead, and zinc in water, sediment, and biota. We measured concentrations of As, Cd, Cu, Pb, and Zn in biofilm and macroinvertebrates, and assessed macroinvertebrate assemblage and aquatic habitat with the objective of monitoring planned remediation efforts. Concentrations of metals were generally higher in downstream sites compared with upstream or reference sites, and two sites contained metal concentrations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 15 publications
2
8
0
1
Order By: Relevance
“…Thus, Heptageniidae may be useful in streams in this region for assessing metal impacts. Other studies have suggested Heptageniidae as sentinel organisms for metal impacts in Rocky Mountain streams (Kiffney andClements 1994, Clements 2000), changes in proportions of major groups and abundance of sensitive taxa as indicators (Clements 1994), and total number of taxa (Rhea et al 2004) and number of EPT taxa as effective metrics for metal impacts (Maret et al 2003). Our data seem to agree with results from these studies.…”
supporting
confidence: 91%
“…Thus, Heptageniidae may be useful in streams in this region for assessing metal impacts. Other studies have suggested Heptageniidae as sentinel organisms for metal impacts in Rocky Mountain streams (Kiffney andClements 1994, Clements 2000), changes in proportions of major groups and abundance of sensitive taxa as indicators (Clements 1994), and total number of taxa (Rhea et al 2004) and number of EPT taxa as effective metrics for metal impacts (Maret et al 2003). Our data seem to agree with results from these studies.…”
supporting
confidence: 91%
“…Cd bioaccumulated these metals reaching values 1-2 orders of magnitude higher than the non-metal-exposed communities. Metal bioaccumulation can have adverse effects for fish and invertebrates that prey on it due to biomagnification (Rhea et al, 2006;Farag et al, 2007;Hill et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperaccumulation of various metals by different plant species with some of these metals being partitioned to the shoots, roots is much of importance for environmental implications. The macroinvertebrate assemblage and aquatic habitat were assessed with the objective of monitoring remediation efforts based on the measurement of concentrations of As, Cd, Cu, Pb, and Zn in biofilm and macroinvertebrates from the Boulder River Watershed, MT, USA [139]. Phytoremediation may also play key roles in preventing metal mine waste from further environmental degradation, as reviewed by Das and Maiti.…”
Section: Bioremediationmentioning
confidence: 99%
“…
a n a l y t i c a c h i m i c a a c t a 6 0 6 ( 2 0 0 8 ) [135][136][137][138][139][140][141][142][143][144][145][146][147][148][149][150] a v a i l a b l e a t w w w . s c i e n c e d i r e c t .
…”
unclassified